Liminal identity in the cooperative organization: A systematic literature review and future research agenda - Alzate, Julieth; Gonzales-Miranda, Diego René (REVESCO. Revista de Estudios Cooperativos, 2025)
This study delves into the liminal state of cooperative organization. As a category from processual anthropology, liminality is used to analyze the identity phenomena in the field of organizational studies. This review has been guided by the purpose of providing a global overview of the literature concerning cooperative identity from the approach of organizational identity in the liminal state and its phases. The review is conducted in two major stages: heuristic and hermeneutic, which are divided into five moments of Denyer & Tranfield’s protocol. For data collection and analysis, this work is supported by the use of tools such as PRISMA statement, Mendeley, ATLAS.ti, and VOSviewer. After analyzing the literature, four broad groups of results emerge: 1) A scoping review presenting the theories, methods, geographies and problems most addressed in the literature, which suggest that cooperative identity is a device for preserving the sector, for governance and social transformation; up to its legalistic and functionalist role for efficiency. 2) The common categories between liminal identity and cooperative identity, based on the three phases of the liminal state: separation, transition, and aggregation. 3) The gap in the literature and its relationship with the interdisciplinary dimension of identity: philosophy, psychology, sociology, management, and anthropology. 4) A consolidation of the future research agenda, highlighting cooperative identity in relation to contemporary technological and social revolutions, the global agenda, among others. Finally, the findings support the premise of the liminal phenomenon in cooperatives and how that has experienced an entropic and liminal state characterized by discrepancies, ambiguity, and indeterminacy inherent in the paradox of the dual nature of cooperative organizations and the current macrostructural context. The reviewed literature revealed that other authors have been interested in studying phenomena implicitly related to one phase of liminality, that is, the process of transition between old and new cooperative identity. Then, some claims for new cooperative identities have shifted the financial–social balance.